Interdisciplinary research in teaching and learning - Laure, Maruša (knjige, 2024)
The monograph titled "Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches," brings together 37 original scientific articles that explore the multifaceted dimensions of education. The contributions span a wide range of topics including innovative teaching methodologies, the integration of technology in learning, competency development, and educational psychology. Each article provides a unique perspective on how interdisciplinary approaches can enhance educational practices and outcomes. The collection aims to bridge theoretical insights with practical applications, offering valuable information for educators, policymakers, and researchers. By addressing contemporary challenges and proposing solutions, this monograph serves as a comprehensive resource for those seeking to understand and improve the complex landscape of modern education. The diverse viewpoints and rigorous research presented herein underscore the importance of collaborative efforts in advancing teaching and learning across various educational contexts.